Meta Analysis: The Impact of Digital Media on Indonesia Language Learning Outcomes in Elementary and Secondary Schools in Indonesia - Charlina Charlina; Elvrin Septyanti; Tria Putri Mustika (AL-ISHLAH: Jurnal Pendidikan, 2025)
The integration of digital media in education has become essential in addressing curriculum and pedagogical challenges in the digital era. This study investigates the impact of digital media on Indonesian language learning outcomes in elementary and secondary schools across Indonesia. This research employed a systematic literature review and meta-analysis following the PRISMA framework. Articles were sourced through Publish or Perish, utilizing databases such as Google Scholar and Scopus. A total of 200 studies were initially identified, and 10 met the inclusion criteria based on relevance, data completeness, and publication year (2017–2022). Quantitative synthesis was conducted using a fixed-effect model and analyzed via JASP 0.19.1 to determine the effect size. The meta-analysis revealed an average effect size of 0.885, indicating a moderate effect of digital media on student learning outcomes. The studies analyzed focused on cognitive (e.g., reading and learning outcomes), psychomotor (e.g., writing and speaking skills), and limited affective domains (e.g., interest in learning). No studies reported negative impacts, and results showed high consistency (I² = 0%). Digital media, particularly animated videos and digital books, positively influence Indonesian language learning at the primary and secondary levels. However, most studies emphasize cognitive outcomes, with minimal exploration of affective or psychomotor domains. These findings suggest a need for broader and more integrative approaches in future research and practice. Digital media moderately enhance language learning outcomes in schools. Further efforts are needed to explore its impact across all learning domains and optimize its educational implementation.